Crystal structure of dichlorido-bis(4-methylphenyl-κC 1)tin(IV), C14H14Cl2Sn - Lo, Kong Mun *; Lee, See Mun *; Tiekink, Edward R. T. * (De Gruyter, 2021)
C14H14Cl2Sn, orthorhombic, P212121 (no. 19), a = 8.2912(1) Å, b = 9.6221(1) Å, c = 18.5616(2) Å, V = 1480.82(3) Å3 , Z = 4,Rgt(F) = 0.0142, wRref(F2) = 0.0347, T = 100 K.